Strengthening Data Literacy and Packaging Efficiency in Food MSMEs through Statistical Approaches in Koto Tangah District, Padang - Mira Meilisa; Hariyadi Hariyadi; Fitri Kurnia; Dytchia Septi Kesuma; Ade Usra Berli; Rahmat Jordan; Praja Purnama Nusa; Muhammad Farhan Al Azfar (Fakultas MIPA Universitas Negeri Padang, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the Indonesian economy, particularly in the food sector. However, many food MSMEs face challenges in managing supply risks, business data recording, and product packaging. This service program aims to strengthen data literacy, improve packaging efficiency, and assist in meeting business legalities for five food SMEs in Parupuk Tabing, Koto Tangah, Padang. Through the Participatory Action Research (PAR) approach, this program focuses on three main interventions: (1) data recording and stock management training, (2) introduction to vacuum packaging technology, and (3) fulfilling business legality requirements by obtaining NIB, PIRT, and halal certification.The results show significant changes, including increased business legality (all MSMEs now have NIB and PIRT), the use of vacuum packaging, and the implementation of regular recordkeeping. This program demonstrates that, in the context of MSMEs with limited data, the statistical approach begins with record-keeping habits and simple information systems as a foundation for further analysis.